Rayleigh-Taylor instability in oscillating liquid pistons. (February 2019) - Langdon-Arms, Samuel; Gschwendtner, Michael; Neumaier, Martin
In this study, an experimental apparatus is used to excite four U-tube-shaped liquid pistons connected in series, and to study their behaviour. Some of the gas spaces are heated to induce piston oscillations; in others, gas expansion is utilised to produce a refrigeration effect. It was discovered that the liquid piston surface would become unstable and turbulent at relatively low gas charge pressures (2 bar–3 bar). Cylindrical polyethylene floats were employed at each piston surface in order to reduce the area of the free surface of each piston and allow experiments to be conducted over a wide range of operating conditions. Experiments were carried out using gas charge pressures in the range of 1 bar–6 bar. The resulting liquid piston oscillations were measured and analysed to assess the impact of any developing piston instability. Evidence of a liquid piston acceleration limit, likely resulting from the Rayleigh-Taylor instability phenomenon, is consistently observed during the experiments. The use of submerged polyethylene piston floats is found to increase the surface stability and enable maximum accelerations of 25 ms −2 to 30 ms −2 .